GST Enzyme Content of Wheat Landraces and Comparison with Modern Varieties - Aziz Öz; Alaettin Keçeli (Turkish Journal of Agriculture: Food Science and Technology)
The development of high-yielding modern wheat varieties to feed the growing population has had a negative impact on the production of ancestral and landrace crops. The use of modern varieties, which are very deficient in vitamins, minerals, antioxidants, and flavonoids, has caused people to turn to old varieties due to health problems that arise over time. In this study, which aimed to determine the glutathione S-transferase (GST) enzyme activity of registered varieties and landraces, the differences between the protein values and GST enzyme activity values of wheat were found to be statistically significant. When protein values were analysed among wheat varieties, einkorn wheat had the highest value with 15.53 mg/ml, and KUNDURU-1149 had the second highest value with 13.52 mg/ml. The lowest protein values were found in wheat landraces. Lr-4 had the highest GST enzyme activity with 299.7 mmol/min/mg protein and Lr-10 with 265.3 mmol/min/mg protein. A negative and high correlation was found between wheat protein values and GST enzyme activity, and it was determined that landraces were prominent in terms of GST enzyme activity.